Effects of 3D microstructure of porous media on DNAPL migration and remediation by surface active agents in groundwater - Zhou Cheng; Ming Wu; Yanru Hao; Cehui Mo; Qusheng Li; Jianfeng Wu; Jichun Wu; Bill X. Hu; Guoping Lu (Eco-Environment & Health)
Aquifers composed of porous granular media are important to human beings because they are capable of storing a large amount of groundwater. Contaminant migration and remediation in subsurface environments are strongly influenced by three-dimensional (3D) microstructures of porous media. In this study, fractal models are developed to investigate contaminant transport and surfactant-enhanced aquifer remediation (SEAR) for the regular tetrahedron microstructure (RTM) and right square pyramid microstructure (RSPM). The relationships of permeability and entry pressure are derived for these two kinds of 3D microstructures of granular porous media. Afterward, the difference in perchloroethylene (PCE) migration and SEAR efficiency between RTM and RSPM is investigated by the numerical simulation based on a synthetic heterogeneous granular aquifer. Results indicate that PCE penetrates faster and spreads farther in RSPM-based aquifers compared with RTM-based aquifers. Further, SEAR in RTM-based aquifers can achieve remediation efficiencies of 66.129%–92.214% with a mean of 84.324%, which is clearly lower than the SEAR efficiency of 70.149%–94.773% (with a mean of 89.122%) in RSPM-based aquifers. Findings are significant for understanding the 3D microstructure of porous media and how the microstructure of porous media affects macroscopic contaminant behaviors and remediation.